EPortfolio: The Scholarly Capstone for the Practice Doctoral Degree in Occupational Therapy - Jim Hinojosa; Tsu-Hsin Howe (Scholarworks @ WMU, 2016)
A critical decision doctoral faculty must make is deciding what is the most appropriate capstone or terminal requirement for the practice doctorate degree that is consistent with the program's curriculum. EPortfolios are a viable option for documenting doctoral students' advanced knowledge and competence. After creating a professional development plan, the students record individual experiences and reflections framed by a selfselected metaphor, provide objective documentation of achievements, and verify advanced competence in a specific area in their ePortfolios. As the students construct their ePortfolios, they must engage in self-directed learning that is grounded in evidence-based and reflective practice, with a focus on developing professional characteristics. The purpose of this article is to describe the rationale and process of using an ePortfolio as the terminal requirement for a practice doctorate degree in occupational therapy.